Parasitic examination of marine ornamental fish at the Denpasar Fish Quarantine, Quality Control, and Fishery Product Safety Center - Nastiti, Amayliana Ajeng (Generasi Biologi Indonesia, 2024)
The study in this research includes examination of parasites in ornamental seawater fish pathologically and clinically which includes examination of mucus, fins, intestines, and gills. This research was conducted at BKIPM Denpasar from January 06, 2020 to February 7, 2020. The samples of marine ornamental fish examined consisted of ornamental fish from various species including Chrysiptera sp., Pterapogon sp., Chromis sp., Amphirion sp., Dascyllus sp. The results showed that the types of parasites that attacked marine ornamental fish were Tricodina sp., Opegaster sp., Archigetes sp., and Camallanus sp. These four types of parasites came from 6 samples from a total of 40 samples examined at BKIPM Denpasar. The total prevalence of infecting parasites was 0.15%. Meanwhile, the prevalence of each species is 0.16% for Tricodina sp. and Opegaster sp. while for Archigetes sp. and Camallanus sp. is 0.33%. Based on the results of the prevalence calculation, the examined seawater ornamental fish samples are still classified as safe for export.